Posterior transpedicular screw fixation of subaxial vertebrae: Accuracy rates and safety of mini-laminotomy technique - Celikoglu, Erhan; Borekci, Ali; Ramazanoglu, Ali; Cecen, Dilber; Karakoc, Abdullah; Bektasoglu, Pinar (Asian Journal of Neurosurgery, 2019)
Background and Aim: Posterior cervical transpedicular screw fixation has the strongest resistance to pullout forces compared with other posterior fixation systems. Here, we present a case on the use of this technique combined with a mini-laminotomy technique, which serves as a guide for accurate insertion of posterior cervical transpedicular screws. Materials and Methods: We retrospectively analyzed data from 40 patients who underwent this procedure in our clinic between January 2014 and March 2017. Results: The study population comprised 27 males (67.5%) and 13 females (32.5%) aged 15–80 years (median, 51.5 years). Surgical indications included trauma (n = 18, 45%), degenerative disease (n = 19, 47.5%), spinal infection (n = 2, 5%), and basilar invagination due to systemic rheumatoid disease (n = 1, 2.5%). In the 18 trauma patients, 14 short-segment (1–2 levels) and 4 long-segment (≥3 levels) posterior cervical instrumentation and fusion procedures were performed. The mini-laminotomy technique was used in all patients to insert, direct, and achieve exact screw fixation in the pedicles. Pedicle perforations were classified as medial or lateral and were also graded. Among the 227 cervical pedicle fixations performed, 48 were at the C3 level, 49 at C4, 60 at C5, 50 at C6, and 20 at C7. Axial computed tomography scan measurements showed that 205 of 227 (90.3%, Grade 0 and 1) screws were accurately placed, whereas 22 (9.69%, Grade 2 and 3) were misplaced. However, no additional neurological injury due to misplacement was observed. Conclusion: As negligible complications were observed when performed by experienced surgeons, the mini-laminotomy technique can be safely used for posterior transpedicular screw fixation in the subaxial vertebrae for single-staged fusion.
Keywords: Mini-laminotomy technique; posterior cervical transpedicular screw fixation; subaxial vertebrae